The Comprehending the Meaning on Song Lyrics “There She Goes” through Interpersonal Metafunctions: A Case on Systemic Functional Linguistics - Silalahi, Tiodora Fermiska; Purba, Ridwin; Silaban, Gabriella Clarisa; Purba, Igna Mariana; Marbun, Elisa May Yolanda; Herman, Herman; Tannuary, Arwin (Bulletin of Science Education, 2024)
This article discusses the Interpersonal Metafunction contained in the lyrics of the song Lee Anthony Marvers’ “There She Goes”. And the purpose of this article is to explain the structure of the lyrics of the song "There she goes" using the interpersonal Metafunction structure method. This type of article applies a qualitative method, namely analyzing the contents of the song lyrics. The steps in analyzing the lyrics of the song "there she goes" are as first the researcher understands the meaning of the lyrics of the song, the second researcher divides the song lyrics into several clauses, the third the researcher classifies each of these clauses according to the structure of the interpersonal metafunction such as (Subject, Finite, Predicator, Adjunct, Compliment), and finally the researcher analyzes the mood and residue. The lyrics of the song "There She Goes" provide an information function or meaning to the readers and listeners of the song. Based on the results of the study, the researchers concluded that the interpersonal function is useful in the implementation of interpersonal communication and provides a complete understanding of the use of mood and residue. Keywords: Interpersonal Metafunction, Systemic Functional Linguistics, Comprehending Meaning Lyric